Enterovirus-D68 – a reemerging non-polio enterovirus that causes severe respiratory and neurological disease in children - Grizer, Cassandra S.; Messacar, Kevin; Mattapallil, Joseph J. (Frontiers in Virology, 2024)
The past decade has seen the global reemergence and rapid spread of enterovirus D68 (EV-D68), a respiratory pathogen that causes severe respiratory illness and paralysis in children. EV-D68 was first isolated in 1962 from children with pneumonia.Sporadic cases and small outbreaks were reported since then with a major respiratory disease outbreak in 2014 associated with an increased number of children diagnosed with polio-like paralysis. From 2014-2018, major outbreaks have been reported every other year in a biennial pattern with > 90% of the cases occurring in children under the age of 16. With the outbreak of SARS-CoV-2 and the subsequent COVID-19 pandemic, there was a significant decrease in the prevalence EV-D68 cases along with other respiratory diseases. However, since the relaxation of pandemic social distancing protocols and masking mandates the number of EV-D68 cases have begun to rise again culminating in another outbreak in 2022. Here we review the virology, pathogenesis, and the immune response to EV-D68, and discuss the epidemiology of EV-D68 infections and the divergence of contemporary strains from historical strains.Finally, we highlight some of the key challenges in the field that remain to be addressed.